Evaluation of Kuliki Paragliding Karo Facility as Sport Tourism - Brema Bangun; Harry Pramono; Imam Santosa Ciptaning Wahyu (Journal Of Sport Education (JOPE), 2024)
This research is to establish standards and management of Kuliki Paragliding Karo facilities as sport tourism based on the Minister of Tourism and Creative Economy Number 4 of 2021. Qualitative descriptive research applies conservation, interview, and documentation methods to collect data on meeting standards and managing kuliki karo paragliding facilities as sport tourism. The findings of this study are the application of standards carried out by Paragliding Tourism Managers very well, including the arrangement of flight implementation flows, conditions, provision of instructions, and well-managed facilities. The management of kuliki karo paragliding has also built cooperation with the local community, including the authorities, and local residents. In order to be able to implement a continuous development system. Based on the results of the study, it can be recommended to all paragliding tourism stakeholders where tourism management must always evaluate in order to continue to create new works and innovations for the paragliding sports tourism sector, especially in the aspects of safety and visitor experience.